Security, Privacy, and Applied Cryptography Engineering Second International Conference, SPACE 2012, Chennai, India, November 3-4, 2012, Proceedings - Bogdanov, Andrey; Sanadhya, Somitra; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Second International Conference on Security, Privacy and Applied Cryptography Engineering held in Chennai, India, in November 2012. The 11 papers presented were carefully reviewed and selected from 61 submissions.  The papers are organized in topical sections on symmetric-key algorithms and cryptanalysis, cryptographic implementations, side channel analysis and countermeasures, fault tolerance of cryptosystems,  physically unclonable functions, public-key schemes and cryptanalysis, analysis and design of security protocol, security of systems and applications, high-performance computing in cryptology and cryptography in ubiquitous devices.
A Novel Circuit Design Methodology to Reduce Side Channel Leakage -- The Schedulability of AES as a Countermeasure against Side Channel Attacks -- Impact of Extending Side Channel Attack on Cipher Variants: A Case Study with the HC Series of Stream Ciphers -- Performance and Security Evaluation of AES S-Box-Based Glitch PUFs on FPGAs -- Relaxing IND-CCA: Indistinguishability against Chosen Ciphertext Verification Attack -- Towards Formal Analysis of Key Control in Group Key Agreement Protocols -- Some Results on Related Key-IV Pairs of Grain -- A Differential Fault Attack on Grain-128a Using MACs -- Breaking Hitag 2 Revisited -- Reduction in Lossiness of RSA Trapdoor Permutation -- Adaptively Secure Efficient Lattice (H)IBE in Standard Model with Short Public Parameters.
Keywords: Computer communication systems; Data encryption (Computer science).; Management information systems; Computer science; Algorithms; Computer security; Computers and civilization; Computer Communication Networks; Cryptology; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Systems and Data Security; Computers and Society